2016
DOI: 10.1016/j.repc.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial fat tissue thickness is increased in patients with lichen planus and is linked to inflammation and dyslipidemia

Abstract: EFT is increased in patients with LP compared to control subjects. Duration of LP is correlated with EFT, and duration of LP is also an independent predictor of increased EFT, which is a predictor of subclinical atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…EFT has an inflammation-inducing effect through the secretion of proinflammatory molecules such as IL-1β, IL-6, tumor necrosis factor (TNF)-α, leptin, plasminogen activator inhibitor-1 and monocyte chemoattractant protein-1 like cytokines [17][18][19]. In this regard, EFT is shown to be increased in psoriasis and lichen planus, compared to the control group, in recent studies [10,11]. SD is seen 2-4 times more frequently than psoriasis and lichen planus in the population [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EFT has an inflammation-inducing effect through the secretion of proinflammatory molecules such as IL-1β, IL-6, tumor necrosis factor (TNF)-α, leptin, plasminogen activator inhibitor-1 and monocyte chemoattractant protein-1 like cytokines [17][18][19]. In this regard, EFT is shown to be increased in psoriasis and lichen planus, compared to the control group, in recent studies [10,11]. SD is seen 2-4 times more frequently than psoriasis and lichen planus in the population [27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that EFT is increased in chronic inflammatory skin diseases such as psoriasis and lichen planus, and is associated with some cardiometabolic parameters in these patients [10,11]. However, no studies to date have investigated EFT in the setting of SD, despite it has been previously shown to be associated with MetS and dyslipidemia [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The systemic infl ammation response-based indexes, such as neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR), were defi ned as an indicator for lichen planus (12,13). Recently, the fi brinogen to albumin ratio (FAR) has been studied as an effective indicator for some cardiovascular diseases, infl ammatory diseases, and malignancies (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of LP and these cardiovascular disorders have been linked with chronic inflammation and the induction of oxidative stress. [21011] Studies have shown an association between LP, dyslipidemia,[234589] impaired glucose tolerance,[12] arrhythmias,[13] hypertension, atherosclerosis,[1415] and MetS. [69] More recently, evidences are increasing on the association between LP, subclinical chronic inflammation, and entities such as carotid media intima thickness and epicardial fat thickness.…”
Section: Introductionmentioning
confidence: 99%
“…[69] More recently, evidences are increasing on the association between LP, subclinical chronic inflammation, and entities such as carotid media intima thickness and epicardial fat thickness. [14151617] The prevalence of MetS, dyslipidemia, and their association with LP varies in published studies. [2345678910] Only a few published studies on MetS and dyslipidemia in LP in the available literature originated from Africa.…”
Section: Introductionmentioning
confidence: 99%